Theoretical estimation of cooling rate value being optimal in terms of two-factor theory of cryodamage when freezing cell suspension by linear regimes - Sakun, A. V.; Gordiyenko, O. I. (Biophysical Bulletin, 2009)
Basing on the general thermodynamic theory of crystal formation the probability of intracellular crystal formation during cooling of yeast like fungi Sacharomyces cerevisiae in cryoprotective solution. A contribution of each of two types of cryodamage associated with extra- and intracellular crystal formation is estimated. Basing on the obtained relations and considering the individual peculiarities of yeast cells the optimal cooling rates for freezing of these cells in the medium with 10% dimethyl sulfoxide cryoprotectant are found. The proposed algorithm for theoretical estimation of optimal value of cooling rate in the linear freezing regimen for the peculiar cell suspension can be utilized when developing the cryopreservation protocols for other biological objects.